Evaluation of forest CO2 fluxes from sonde measurements in three different climatological areas including Borneo, Malaysia, and Iriomote and Hokkaido, Japan. Issue 1 (1st January 2018) - Nomura, Shohei; Mukai, Hitoshi; Terao, Yukio; Takagi, Kentaro; Mohamad, Maznorizan; Jahaya, Mohad Firdaus
Abstract: Evaluation of carbon dioxide (CO2 ) sinks in forest areas of East and Southeast Asia (especially tropical regions) is important for assessing CO2 budgets at the regional scale. To evaluate the CO2 flux of large forest areas, we collected vertical CO2 profiles over the forest using a CO2 sonde and measured surface CO2 concentrations around the forest using continuous CO2 measurement equipment. These observations were performed over a typical northern forest (Hokkaido) in Japan, a subtropical forest island (Iriomote Island) in Japan, and a tropical forest in Borneo Island. We detected the differences in CO2 vertical profiles between dawn and daytime, and at the upwind and downwind sites of the forests with the observational results from the CO2 sonde. We also clarified that CO2 concentrations during daytime at the downwind sites (affected by the forest) were systematically lower than those at the upwind sites (not affected by the forest). In contrast, CO2 concentrations during dawn at the downwind sites were larger than those at the upwind site. We estimated the CO2 fluxes (μmol m −2 s −1 ) at dawn and daytime of the forests from these observational results. The CO2 fluxes of Borneo's forest were very large (16.5 and −37.7 at dawn and daytime, respectively), whereas the CO2 fluxes of the forests in Hokkaido and Iriomote were lower (3.9 to 11.8 at dawn and −11.8 to −15.0 at daytime). These evaluated values were consistent with fluxes measured by the eddy-covariance method in the same region. Thus, use of the CO2 sonde to collect observations of CO2 vertical profiles was considered to be an effective method to verify CO2 absorption and emission in large forest areas. This method can also be used to evaluate dynamic CO2 absorption and emission processes in tropical forests.